Filantropi Dakwah dalam Pandangan Moralitas Agama dan Keadilan di Kalangan Masyarakat - Agustini, Joshe Layyinah; Alvita, Putri (Tadabbur: Jurnal Integrasi Keilmuan, 2023)
History shows that the development of the monotheistic religion can continue to spread because of the continuous efforts of preaching carried out by the prophets and continued by the missionaries until today. The gap between the reality of the condition of Muslims and the ideals expected in Islamic teachings is a major problem that must be resolved immediately. The purpose of this study is to find the relationship between preaching and philanthropy and to develop philanthropy-based preaching. Philanthropic preaching is every effort made to fight for human welfare in terms of economy, education, and social. The method used is qualitative descriptive analysis. The results of this study found the fact of the relationship between preaching and philanthropy in society.